Whole blood RNA-seq analysis reveals the immunomodulatory effects of a supplemental multi-strain direct-fed microbial in the diet of newly weaned beef steers1 - Ajiboye, Adekunle; Johnson, Samanthia; Idowu, Modoluwamu; Leal, Yarahy; Sidney, Taylor; Taiwo, Godstime; Ogunade, Ibukun M.; Ashwell, Christopher (Frontiers in Animal Science, 2025)
We examined the effects of a blend of live Saccharomyces cerevisiae, multiple probiotic bacteria, and their fermentation products on the whole blood transcriptome of newly weaned beef steers during a 56-d receiving period. Forty newly weaned Angus crossbred steers (12-h postweaning; 217 ± 4.6 kg of body weight [BW]; 202 ± 4 d of age) from three different sources were stratified by BW and randomly assigned to one of the two treatments: 1) basal diet with no additive (CON; n = 20), and 2) the basal diet supplemented with 9 g/steer/d of a multi-strain microbial additive (PRO; n = 20). The PRO additive was a blend of S. cerevisiae and the fermentation products of Enterococcus faecium, Bacillus licheniformis, B. subtilis, Lactobacillus animalis, and Propionibacterium freudenreichii. On day 56, 10 mL of blood was collected from 10 randomly selected beef steers from each treatment group prior to morning feeding. Total RNA was isolated from the whole blood samples for the determination of gene expression profiles. Differentially expressed genes (DEGs) were identified using a false discovery rate (FDR) ≤ 0.10. A total of 41 DEGs were detected; 21 genes, including TLR10, GPR183, LGR4, and FCRL1, were upregulated in steers fed the PRO additive compared to CON, while 20 genes, such as C3, DDIT4, and ADCY8 were downregulated. Gene ontology analysis of the DEGs revealed the enrichment (FDR< 0.05) of pathways related to positive regulation of inflammatory response, regulation of cytokine secretion, positive regulation of defense response, and positive regulation of response to external stimuli in beef steers fed PRO additive. No significant differences (P > 0.05) in growth performance (BW, DMI, or ADG) were observed between CON and PRO steers. In conclusion, this study revealed that beef steers fed the PRO additive exhibited differential expression of genes related to immune function and inflammatory response, suggesting an effect on immunity and stress resilience. These findings highlight the potential of multi-strain direct-fed microbials as a nutritional strategy to support immune health, resilience to stress, and overall welfare in beef cattle during the weaning and receiving period.